Contributions of psychoanalysis for psychosocial interventions in armed conflict scenarios (2018)
This article proposes and discusses the possible contributions of psychoanalysis to psychosocial interventions in armed conflict scenarios, not only for psychoanalysts but also for every professional in charge of carrying out this type of interventions. First, historical aspects are analyzed that show the great interest of the first and second generations of psychoanalysts in psychosocial and political issues. After that, 4 main contributions of psychoanalysis to psychosocial interventions are considered: (a) the nonstandardization of trauma, (b) the ethical position of not knowing or not understanding, (c) the respect for logical times, and (d) the invitation to delve into the unknown of ourselves. The paper shows how psychoanalysis allows unique insight into the conceptualization of trauma and how it can contribute to guide the psychosocial interventions in armed conflict scenarios. The author males specific references to the case of Colombia's current peace processes with illegal guerrilla groups and the great challenge implied in offering the appropriate psychosocial interventions to all subjects who have directly or indirectly been affected by the consequences of warfare. © 2017 American Psychological Association.